Provisions on small and medium-sized enterprises in regional trade agreements - José-Antonio Monteiro (World Trade Organization (WTO), 2016)
This paper reviews the different types of provisions explicitly addressing small and medium enterprises (SMEs), including micro firms (MSMEs), in regional trade agreements (RTAs). The analysis covers the 270 RTAs currently in force and notified to the WTO as of April 2016. The analysis shows that half of all the notified RTAs, namely 136 agreements, incorporate at least one provision mentioning explicitly SMEs. These SMEs-related provisions are highly heterogeneous and differ in terms of location in the RTA, language, scope and commitments. Many of the SMEsrelated provisions are only found in a single or couple of RTAs. A limited but increasing number of RTAs incorporate specific provisions in dedicated articles or even chapters on SMEs. Although the number of detailed SMEs-related provisions included in a given RTA has tended to increase in recent years, most SMEs-related provisions remain couched in best endeavour language. The two most common categories of SMEs-related provisions found in RTAs are provisions (1) promoting cooperation on SMEs and (2) specifying that SMEs and/or programs supporting SMEs are not covered by the RTAs' obligations provisions. Other types of SMEs-related provisions, incorporated in a limited number of RTAs, refer, inter alia, to government procurement, trade facilitation, electronic commerce, intellectual property, or transparency.
Keywords: F13; F15; 330; Regional Trade Agreements; Small and Medium-Sized Firms (SME)